La délinquance en milieu aisé : un groupe culture d’adeptes de la drogue - LeBlanc, Marc (Acta Criminologica, 1972)
AbstractDELINQUENCY IN THE MIDDLE CLASS :A GROUP CULTURE OF COMMITTED DRUG USERSAs a first step, this monograph evaluated the literature dealing with middle class delinquency. We were interested in the traditional forms of delinquency — agression, theft, etc., but in new forms as well : the hippie movement and student protest. Our second step was the study of a group culture of young adults, users of the minor drugs, hallucinogenics and psychedelics. This empiric study of the drug phenomenon in the middle class was accomplished by participant observation.The object of analyzing the group culture was to show how the consumption and distribution of drugs condition the structural and cultural aspects of life among a group of drug users. The results showed that the drug consumers studied were not social failures, and that their only consistent manifestation of maladjustment lay in their use of drugs. The group studied was a quasi-group whose activities consisted of sitting around and taking drugs with a background of silence or music. Culturally, much more of a vacuum was to be observed than adherence to an ideological, counter-cultural .— or rather, para-cultural .— support. The most interesting result was the demonstration of the direct relationship between drugs (consumption and/or distribution) and the structural and cultural aspects of the group studied.To interpret this drug phenomenon in the middle class, we advanced a paradigm consisting of four fields of importance : mass society that is alienating and anomic, the place of youth in society, the tolerance toward deviance, and the aimlessness of leisure time. On the basis of these areas of importance, the drug phenomenon exists because of the drift of youth between conformity and deviance.